An approach for location area planning in a personal communication services network (PCSN). - Bhattacharjee, P.S (IEEE Transactions on wireless communications)
This paper deals with an approach for planning location areas (LAs) in a personal communication services network (PCSN) to be overlaid on an existing wired network. Given the average speed of mobile terminals, the number of mobile switching centers (MSCs), their locations, call handling capacity of each MSC, handoff cost between adjacent cells and call arrival rate, an important consideration in a PCSN is to identify the cells in every LA to be connected to the corresponding MSC in a cost effective manner. In this work, while planning a location area, we present a two-step approach, namely optimization of total system recurring cost (subproblem I) and optimization of hybrid cost (subproblem II). The planning first determines the optimum number of cells in an LA from subproblem I. Then, it finds out the exact LAs by assigning cells to the switches, while optimizing the hybrid cost which comprises the handoff cost and the cable cost, in subproblem II. This divide-and-conquer strategy provides a practical way for designing LAs. As our approach toward LA planning takes into accounts both cost and network planning factors, this unique combination will be of great interest to PCSN designers. It develops an optimum network planning method for a wide range of call-to-mobility ratios that minimizes the total system recurring cost while still ensuring a good system performance. Our study shows that acceptable results are achievable with a reasonable computational effort, which supports the engineered planning of a PCSN.